TIK TOK AS A PROMOTIONAL MEDIA TO INFLUENCE CONSUMER PURCHASE DECISIONS - Martini, Luh Kadek Budi; Suardhika, I Nengah; Dewi, Luh Komang Candra (Universitas Brawijaya, Indonesia, 2022)
The main purpose of this study is to analyze Tik Tok media as the main consideration in purchasing decisions for culinary products and Tik Tok as a medium for promoting culinary products to purchase decisions. This research was conducted in Denpasar City with a sample of 120 respondents. The data was collected using Google Forms. Data were analyzed qualitative and quantitative using a Likert scale. Inferential statistical analysis was used to draw inference from the sample to the population and hypothesis testing using Partial Least Square (PLS) with Smart-PLS 3.0. The study results found that the more informative the promotion with social media on the Tik Tok application, the more buying interest and ultimately convincing consumers to purchase. Purchase intention has a full mediation effect on the informative indirect effect on purchasing decisions for culinary products.